Analysis of Financial Performance and Macroeconomics on Profitability of Islamic Banking In Indonesia - Mustofa, Nadian; Sukardi, Agung Slamet (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study explores how financial parameters (CAR, NPF, OER, NOM, FDR) and macroeconomic variables (Inflation, BI Rate, GDP) affect Indonesian Islamic commercial banks' profitability (ROA). Previous research have found inconsistent effects of these factors. This research seeks to discover key elements affecting Islamic bank profitability. All elements boost Islamic commercial bank profitability. Utilizing secondary data sourced from Islamic banks registered with the OJK and macroeconomic variables covering the period from Q1 2018 to Q2 2024, quantitative analysis with multiple regression is applied. Three Islamic institutions were chosen using purposive sampling, and the study was carried out using SPSS version 30. According to the results, ROA is positively and significantly affected by NPF, OER, and CAR, but not by NOM, FDR, inflation, BI Rate, or GDP. These findings point to the fact that operational efficiency and finance risk management have a more substantial impact on the profitability of Islamic organizations.